(untitled) (Encuentros, 2024)
The Analytical Geometry subject of Colombian high school does not have a written history, despite having exceptional importance in the development of time-space thinking and metric systems, since in this course activities related to the analysis of distances are studied between points, projectile movements, navigation systems, current issues of georeference, satellite location, GPS, among other issues that potentially involve time-space relationships that were not worked on in the preceding courses of school training. It is intended to show the legislative and curricular history of this course, in the sense of showing or analyzing the international context that gave its origin, as well as the different decrees, resolutions, and theoretical supports that could be found and that little by little were giving shape to what nowadays is known as 10 ° Analytical Geometry.